2020
DOI: 10.3390/ani10081245
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Recombinant Antigens in the Serodiagnosis of Toxoplasmosis in Domestic and Farm Animals

Abstract: Toxoplasmosis is caused by an intracellular protozoan, Toxoplasma gondii, and is a parasitic disease that occurs in all warm-blooded animals, including humans. Toxoplasmosis is one of the most common parasitic diseases of animals and results in reproductive losses. Toxoplasmosis in humans is usually caused by eating raw or undercooked meat or consuming dairy products containing the parasite. Diagnosis of toxoplasmosis is currently based on serological assays using native antigens to detect specific anti-T. gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 111 publications
0
25
0
Order By: Relevance
“…At all infection doses, ROP4 VLP antigen showed higher IgG antibody responses compared to TLA antigen at 1, 2, 4, and 8 week PI, indicating that antibody induction from even a very low infectious dose can be detected using ROP4 VLP antigen. Importantly, we found that at higher infectious dosage (150 and 300 cysts), ROP4 VLP antigen showed higher IgG antibody responses as early as 1 week PI, which was not reported by using other recombinant proteins [ 12 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…At all infection doses, ROP4 VLP antigen showed higher IgG antibody responses compared to TLA antigen at 1, 2, 4, and 8 week PI, indicating that antibody induction from even a very low infectious dose can be detected using ROP4 VLP antigen. Importantly, we found that at higher infectious dosage (150 and 300 cysts), ROP4 VLP antigen showed higher IgG antibody responses as early as 1 week PI, which was not reported by using other recombinant proteins [ 12 ].…”
Section: Discussionmentioning
confidence: 62%
“…Sf9 cells were co-infected with the M1-rBVs and ROP4-rBVs to generate ROP4 VLPs. Afterward, VLPs were purified through a discontinuous sucrose gradient centrifugation and stored at −80°C until use as described previously [ 12 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final host, cats play an important role in spreading T. gondii infection [3]. Therefore, poor hygienic management of farms, climate, presence of cats in farms, consuming raw or uncooked meat and vegetables, and inter-current diseases may act as potential risk factors influencing this disease [4].…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasmosis is caused by the protozoan parasite Toxoplasma gondii , where >60% of populations are infected with these parasites ( 1 , 2 ). The infection often occurs in areas of lower altitudes, hot and humid climates ( 2 ).…”
Section: Introductionmentioning
confidence: 99%